Factors of enterprise resource planning implementation among small and medium-sized enterprises: a systematic literature review - Wang, Zhi Ming (2019)
Nowadays, with the continuous development of economic globalization, the competition faced by various enterprises is increasing. Whether it is a small, medium or large enterprise, their daily operations generate a lot of data, and their business processes are more and more complex, requiring more advanced tools for inventory management, resource management and so on. As an enterprise integrated information system, Enterprise Resource Planning (ERP) can effectively assist enterprises to integrate daily data and information of enterprises, and ultimately improve the business efficiency of various departments and enhance the competitiveness of enterprises. However, for Small and Medium-Sized Enterprises (SMEs), although there is a lot of evidence that ERP has many benefits for them, there are still many SMEs that refuse to implement ERP, and many companies cannot successfully implement ERP. In this regard, a large number of scholars have studied the factors affecting the implementation of ERP in different enterprises, and there are many studies on SMEs. However, it is difficult to find systematic and comprehensive research on the factors affecting the implementation of ERP in SMEs. Therefore, this study aims to fill the gap by providing a systematic literature review related ERP implementation in SMEs. The search and refinement stages in this review study were carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). The articles covered in this study were mainly selected from two electronic databases, Web of Science and Scopus. After screening, 41 articles were eventually reviewed. Based on these reviewed articles, this study found that the main factors affecting the implementation of ERP in SMEs are organizational factors, technical factors, environmental factors and other factors. The theoretical model commonly used in these reviewed articles is the Technology-Organization-Environment (TOE) framework and the Technology Acceptance Model (TAM). The main research methods are survey and case study. This study also found that organizational-related factors were considered by many articles to be the main factors affecting the implementation of ERP in SMEs.